The Analysis of Road Performance in Tiban Indah Batam, Indonesia - Reinaldy Jastino; Yusra Aulia Sari (LEADER: Civil Engineering and Architecture Journal, 2023)
Traffic Congestion is one of the main problems in cities. Although traffic congestion can be a significant problem in a city, most of the time, it only happens during working hours, when people go to work and go home. The research aims to analyze the road performance of Jalan Gajah Mada in the Tiban Indah Area. The data was collected using surveying methods that follow the IHMC (1997) guidelines on Monday, 21st November 2022, from 5 until 6 p.m. for one hour with an interval of 15 minutes. To summarize the conclusion, the analyzed total traffic flow during peak hour is 3,975.75 pcu/hour, a total capacity of 6,468 pcu/hour, and attained a degree of saturation of 0.615, resulting in a level of service C.